TAHAP PENGEMBANGAN BAHAN AJAR “CREATIVE FACTOR” BERBASIS PROYEK PADA MATERI KELIPATAN DAN FAKTOR BILANGAN DIKELAS IV SEKOLAH DASAR - Ina Riana; Rida Fironika Kusumadewi; Nuhyal Ulia (Jurnal Riset Pendidikan Dasar (JRPD), 2020)
Abstrak. This research is to develop and find out the feasibility of "Creative Factor" teaching material products on multiples and number factors. "Creative Factor" teaching material products multiples and number factors are developed based on the teacher's need for other reference sources in learning. This research uses the Research and Development (RnD) method. The development of "Creative Factor" teaching material products uses a development research procedure according to Sugiyono that contains 10 thrones. Based on this, the research results obtained include: (1) the validation results from 4 experts obtained an average score of 84 and a percentage of 90% with the criteria "Very Eligible". (2) the results of the small-scale test get teacher responses obtained by the percentage of 88% with the criteria "Very Practical". While the results of student responses obtained 97.2% percentage "Very Practical". (3) large-scale test results obtained by teacher responses obtained by the percentage of 90% with the criteria "Very Practical". While the results of student responses obtained 96% percentage "Very Practical". Based on these results, the development of "Creative Factor" teaching material products can be declared worthy to be used as a companion in the learning process.